2019
DOI: 10.1111/inm.12632
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of mobile information and communication technologies by people with mood disorders

Abstract: Information and communication technologies (ICTs) have become increasingly integrated into how care is delivered and received. However, no research has yet explored how people with mood disorders use mobile information and communication technologies (mICTs) in their everyday lives and, more specifically, how they might use mICTs to look after themselves. An exploratory qualitative study, within secondary and specialist mental health Services, was undertaken. Data generation involved in‐depth, semi‐structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 125 , 126 However, previous research has noted how monitoring and tracking can negatively impact patients’ quality of life 148 by being overwhelming, 117 incompatible with daily life, 149 and in opposition to patients’ need to maintain control and establish normalcy. 150 Moreover, medicalized devices that provide continuous monitoring may counter the needed distraction that may be beneficial for reducing negative moods, 151 and detract from DTs’ role in distancing from negative thoughts 152 , 153 when facing the uncertainty of the disease trajectory. Below we examine how participants use of DTs for intergenerational connections, leisure, and other activities outside of their illness provides multiple avenues for distancing from negative thoughts.…”
Section: Discussionmentioning
confidence: 99%
“… 125 , 126 However, previous research has noted how monitoring and tracking can negatively impact patients’ quality of life 148 by being overwhelming, 117 incompatible with daily life, 149 and in opposition to patients’ need to maintain control and establish normalcy. 150 Moreover, medicalized devices that provide continuous monitoring may counter the needed distraction that may be beneficial for reducing negative moods, 151 and detract from DTs’ role in distancing from negative thoughts 152 , 153 when facing the uncertainty of the disease trajectory. Below we examine how participants use of DTs for intergenerational connections, leisure, and other activities outside of their illness provides multiple avenues for distancing from negative thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…The robustness of the smart mHealthcare system leverages the potential benefits in the reduction of complexity in the HCI environment. The smart mHealthcare HCI design is based on the UCD mitigate the reliance and reluctance on limited healthcare infrastructure and speed up the healthseeking practice [13]. This is why good care and better health results become the ultimate goal of the overall healthcare environment.…”
Section: Introductionmentioning
confidence: 99%
“…There are also numerous qualitative research studies that have demonstrated the importance of mobile technologies to facilitate the treatment and recovery of mood disorders. For instance, several studies have identified the role of mobile app use on helping with patients' social interconnectivity, skill acquisition, access and management of needs, and bridge the disconnection with health professionals ( Fulford et al, 2019 ; Pung et al, 2018 ). Other studies have revealed factors that might influence the effectiveness or motivation of mobile mental health services usage, such as mental health awareness, appropriate content and medium, functionality, human support, reminders or incentives ( Eccles et al, 2020 ; Simblett et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%